Multi-stakeholder communication and coordination systems in post-disaster socio-economic recovery collaboration - Mochammad Rozikin (Jurnal Studi Komunikasi, 2024)
This study explores the crucial role of multi-stakeholder communication and coordination systems in the socio-economic recovery collaboration implemented in East Lombok, Indonesia following a significant disaster. Using a qualitative research approach, this paper examines the interactions and communication dynamics among various stakeholders, including government agencies, non-governmental organisations, local communities, and the private sector. The research highlights the importance of effective communication and coordinated efforts in rebuilding the socio-economic fabric of disaster-affected areas. Findings indicate that collaborative frameworks significantly enhance the efficiency and effectiveness of recovery processes, fostering resilience and sustainable development. The study also identifies key challenges such as resource allocation, stakeholder coordination, and cultural barriers which can impede recovery efforts. Recommendations are provided for improving communication strategies, stakeholder engagement, and policy implementation to strengthen post-disaster recovery initiatives. This research contributes to the field of communication studies by offering insights into the dynamics of multi-stakeholder collaboration in disaster recovery, emphasising the need for integrated and inclusive approaches to achieve long-term socio-economic stability and growth.